Determinan Kejadian Loss to Follow Up Pengobatan Antiretroviral (ARV) Pada Pasien HIV/AIDS di RSUD Khidmat Sehat Afiat Kota Depok Tahun 2025 - Putri, Novia Fatmawati; Tanesib, Amran Julianto; Herdayanti, Mila (Jurnal Epidemiologi Kesehatan Komunitas, 2025)
Background: RS “X” Depok City recorded that around 13,054 people living with HIV (PLWHA) have accessed antiretroviral (ARV) services until 2025. However, until now there has been no research related to Lost to Follow Up (LTFU) in Depok City Hospital “X”. Research is needed to determine the determinants of the incidence of LTFU of ARV treatment, especially in HIV/AIDS patients at “X” Depok City Hospital.Methods: T This study used a quantitative approach with a cross-sectional design. The population in this study were all patients who had accessed ARV treatment services at “X” Hospital in Depok City in 2024. The sample in this study was 312 PLWHA obtained using simple random sampling technique. The dependent variable in this study was the incidence of LTFU, while the independent variables included age, gender, place of residence, referral origin, duration of ARV consumption and population group. Data were analyzed using univariate, bivariate and multivariate analysis with p<0.05 and 95% confidence level.Results: The results showed that 44.2% of HIV/AIDS patients at RS “X” Depok City experienced LTFU. The variables of residence and referral origin were significant predictors of the incidence of LTFU in HIV/AIDS patients at RSUD “X” Depok City.Conclusion: There needs to be assistance for HIV/AIDS patients who live in Depok City and HIV/AIDS patients who come alone without a referral so that they can continue to undergo ARV treatment continuously.Keywords: Antiretroviral, HIV, AIDS, Loss to Follow Up